Terorisme Dalam Perspektif Jurgen Habermas - Fatih, Moh. Khoirul (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
The study of terrorism today still raises various problems, aside from the factors that are considered to have an important role in the emergence of terrorism which is now the investigation of experts from various scientific disciplines, also no less important is the definition of terrorism itself. Debate about the definition of terrorism is still difficult to reach an agreement, even though the definition is important for the filter of certain types of actions and groups to be included or not in the terrorism category. Jurgen Habermas is a man who has a variety of thoughts related to humanities, the presence of Habermas in the list of names of Western thinkers brings something new to the renewal of Western theory. Appear as a brilliant figure in formulating critical theory. Jurgen Habermas gave a new look that was more critical, including giving a critical view of the terrorist events that occurred. according to Jurgen Habermas, which can lead to the emergence of terrorism is because it is distorted in communication. In addition to modernity, secularization can also lead to violence where fundamentalism wants the return of traditional styles, where religion can expand in everything. For example, contemporary regimes in Iran or religiously inspired movements are struggling to build a theocracy